1995
DOI: 10.1016/0092-8674(95)90461-1
|View full text |Cite
|
Sign up to set email alerts
|

The gene for neuronal apoptosis inhibitory protein is partially deleted in individuals with spinal muscular atrophy

Abstract: The spinal muscular atrophies (SMAs), characterized by spinal cord motor neuron depletion, are among the most common autosomal recessive disorders. One model of SMA pathogenesis invokes an inappropriate persistence of normally occurring motor neuron apoptosis. Consistent with this hypothesis, the novel gene for neuronal apoptosis inhibitory protein (NAIP) has been mapped to the SMA region of chromosome 5q13.1 and is homologous with baculoviral apoptosis inhibitor proteins. The two first coding exons of this ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
554
1
8

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 899 publications
(592 citation statements)
references
References 40 publications
25
554
1
8
Order By: Relevance
“…56 Despite the absence of a CARD, the neuronal apoptosis inhibitor protein (NAIP) shares with IPAF the highest sequence similarity of the NACHT and LRR domains, suggesting that these molecules are evolutionary and functionally related. 57 Instead of a CARD, NAIP harbors three N-terminal baculovirus inhibitor-of-apoptosis repeats (BIR), 58 which were proposed to act as caspase inhibitors. 59 Mutations in NAIP are associated with the development of spinal muscular atrophy.…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
See 1 more Smart Citation
“…56 Despite the absence of a CARD, the neuronal apoptosis inhibitor protein (NAIP) shares with IPAF the highest sequence similarity of the NACHT and LRR domains, suggesting that these molecules are evolutionary and functionally related. 57 Instead of a CARD, NAIP harbors three N-terminal baculovirus inhibitor-of-apoptosis repeats (BIR), 58 which were proposed to act as caspase inhibitors. 59 Mutations in NAIP are associated with the development of spinal muscular atrophy.…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…59 Mutations in NAIP are associated with the development of spinal muscular atrophy. 58 Mouse NAIP is mainly expressed in macrophages and is encoded by seven paralogous genes, naip1 to naip7. 60 NAIP was proposed to interact with IPAF indicating that it may be part of the same caspase-1 activating complex 61 (Figure 2).…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…It has also been reported that apoptosis may have a critical role in neuodegenerative diseases (Gschwind and Huber, 1995;Roy et al, 1995;Ham et al, 2000).…”
mentioning
confidence: 94%
“…Human NAIP lies within a tract of four other genes that have undergone a 500-kb inverted duplication. The duplicated NAIP copy appears to be a pseudogene [17]. This duplication is specific to humans, while in other primates a pericentromeric inversion (chimpanzee and bonobo) and a translocation to Chromosome 19 (gorilla) have repositioned NAIP [18].…”
Section: Introductionmentioning
confidence: 94%